2010
DOI: 10.1103/physrevlett.105.096802
|View full text |Cite
|
Sign up to set email alerts
|

Landau-Level Mixing and the Emergence of Pfaffian Excitations for the5/2Fractional Quantum Hall Effect

Abstract: We report on exact diagonalization studies for fully spin polarized 5/2 fractional quantum Hall effect, incorporating Landau level mixing through the Bishara-Nayak effective interaction. We find that there is an experimentally accessible region in the phase diagram where the Pfaffian model accurately describes not only the ground state but also the neutral and charged excitations. These results are consistent with the observed persistence of the 5/2 Hall effect down to very low magnetic fields; they are also r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 34 publications
(44 reference statements)
3
122
1
Order By: Relevance
“…At the same time, several papers 56,68,76,77 lend support to a spin-polarized ground state. Another limitation comes from the incomplete understanding of the Landau-level mixing effects [78][79][80][81] . Disorder apparently plays a major role in the discrepancy of the theoretical and experimental results for the energy gap 73,82 and may affect the nature of the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, several papers 56,68,76,77 lend support to a spin-polarized ground state. Another limitation comes from the incomplete understanding of the Landau-level mixing effects [78][79][80][81] . Disorder apparently plays a major role in the discrepancy of the theoretical and experimental results for the energy gap 73,82 and may affect the nature of the ground state.…”
Section: Discussionmentioning
confidence: 99%
“…Later in this work we add additional V α terms to V C in order to explore the neighboring phases. In experiment, such variations of the interaction may arise due to Landau level mixing [48,[87][88][89][90][91][92][93][94].…”
Section: A the Bilayer Modelmentioning
confidence: 99%
“…In particular, the stripe phase prevails when there are two states close to the Fermi energy and when the filling of one or both states is very close to the half-filling. Furthermore, numerical calculations [21] showed that the overlap between a specific exact ground state and a Pfaffian state (which is expected to be also responsible for the 7/2 FQHE state in high-density samples) decreased when  > 2, suggesting an instability of the Pfaffian state at low densities. In sample A  = 3.3 at =7/2, much larger than  = 1.3 in the high-density samples of n=310 11 cm -2 , where an isotropic =7/2 FQHE state has been observed.…”
mentioning
confidence: 99%
“…The authors in Ref. [21] did not calculate the overlap between the exact ground state and an anisotropic state. It remains interesting to observe whether under their numerical model the anisotropic state actually becomes more stable in the large  regime.…”
mentioning
confidence: 99%
See 1 more Smart Citation